Effects of synergistic fermentation of tea bee pollen with bacteria and enzymes on growth and intestinal health of Apis cerana cerana - Panpan Xue; Le Xu; Yakai Tian; Mingkui Lv; Pingping Fang; Kun Dong; Qiuye Lin; Zhenhui Cao (Current Research in Microbial Sciences)
While the health benefits of lactic acid bacteria (LAB)-fermented feed on farmed animals are well-established, its potential benefits for honeybees, specifically Apis cerana cerana, remain largely unexplored. The present study aimed to optimize an enzymatic hydrolysis process for tea bee pollen, employing a complex enzyme comprising acid cellulase and pectinase, followed by fermentation with Limosilactobacillus reuteri LP4. A. c. cerana workers were subsequently fed tea bee pollen processed with this optimized method. Under the optimal processing condition of fermented tea bee pollen, the pH value was 4.41, the protein content was 27.75 %, and the viable count of LAB was 2.31×10⁹ CFU/g. No molds and yeasts as well as pathogens were detected. Compared to the unfermented pollen, honey bee workers administrated with fermented tea pollen with L. reuteri LP4 showed significantly increased survival rate by 24.34 % on day 15. Moreover, the relative abundances of Lactobacillus and Bifidobacterium were elevated, while those of Enterococcus and Bacteroides were diminished. Concurrently, the relative expression levels of immune-related genes including Abaecin, PPO, Defensin, and Vg were significantly upregulated. These findings provide a scientific foundation for application of fermented feeds to enhance the health of A. c. cerana populations and contribute to the sustainable development of apiculture in China.